Intrauterine metformin exposure and adiposity outcomes in children: a systematic review and meta-analysis - George Tomlinson; Jill Hamilton; Kellie E Murphy; Jennifer Fu; Najla Tabbara; Denice S Feig (BMJ Open)
Objective The study aims to assess the effect of intrauterine metformin exposure on offspring adiposity measures in childhood.Design Systematic review and meta-analysis.Data sources Medline, Embase and Cochrane Central were searched from inception to 4 October 2024.Eligibility criteria for selecting studies Follow-up studies of randomised-controlled trials and observational studies involving metformin use in pregnancy for any insulin-resistant maternal condition were included.Data extraction and synthesis Two reviewers independently extracted data and completed risk-of-bias assessments using either Cochrane Risk-Of-Bias tool V.2 or Risk of Bias in Non-Randomised Studies of Exposure depending on study design. Meta-analyses were conducted using the generic inversed variance method in a random-effects model. Grading of Recommendations Assessment, Development and Evaluation methodology was used to assess certainty of evidence.Results 18 studies reporting on 7975 children with metformin exposure in utero and over 1 million children without metformin exposure were included. At the oldest age of follow-up reported (weighted mean age of 4.4 years), children with metformin exposure for any maternal indication had comparable body mass index (BMI) with their non-exposed peers (standardised mean difference (SMD) −0.02; 95% CI: −0.11, 0.07; low certainty). When stratified by age at follow-up, while metformin-exposed children had slightly higher BMI at 1–3 years of age (SMD 0.15; 95% CI: 0.04, 0.27; low certainty), no difference remained between the two groups by ages 3–6 and 6–11 years. When stratified by maternal diagnosis, no difference in BMI was found in the diabetes and obesity subgroups, while in the polycystic ovary syndrome subgroup metformin-exposed children were heavier than non-exposed peers (SMD 0.31; 95% CI: 0, 0.62; low certainty). No difference was seen in overweight, obesity or waist circumference.Conclusions Metformin-exposed children did not differ in adiposity measures compared with their non-exposed peers in later childhood. This adds to the growing body of evidence supporting the long-term safety of metformin use in pregnancy.PROSPERO registration number CRD42023394464.